Back Matter - JTSiskom Volume 7 Issue 1 Year 2019 - JTSiskom, Editor in Chief (Jurnal Teknologi dan Sistem Komputer, 2019)
This article contains back-matter of JTSiskom Volume 7 Issue 1 Year 2019, which includes the author's index, author guidelines, copyright notice and its transfer agreement, publication ethics statements and journal content licenses.